Study on Geomorphology of Cepogo Sub-District, Boyolali, Central Java - Purwanto, Ajun (Universitas Muhammadiyah Surakarta, 1997)
There are two point of this geomorphological research. Firstly, to study the characteristic or physical condition of the observed area. Secondly, data providing or geomorphology information extracted from geomorphological map of scale 1 : 25.000. this research included literature study collecting of primary and secondary data. The method applied in this researh was the map interpretation of the observed area. The maps interpretationÂ included topographical, geological, slope, and soil. Fieldwork was carried out to compare the result of maps interpretationÂ with the facts of field, all at once for recording and surveying of the field physical data observed in the research. There were four types of recorded physical data i.e morphology, morphogenesis, morphocronology,, and morphoarrangement. In the research there was known that the observed area consists of an origin landform i.e. formation of volcanic origin and distinguished into nine units of landform. In broad outline, in the observed area of the research, there were many geomorphological processes i.e. weathering, erosion, and massdenudation of rocks, and there were also found steeply slopes deep valleys and formation of alluvial fan.